Transcriptome analysis reveals the mechanism of mixed oligosaccharides in the response of rice seedlings to abiotic stresses - Xu, Yanan; Yang, Yigang; Bai, Yeran; Saito, Makoto; Han, Wei; Zhang, Yuanpei; Lv, Guohua; Song, Jiqing; Bai, Wenbo (Frontiers in Plant Science, 2025)
Salinity and alkalinity stresses severely suppress rice seedling growth and substantially reduce rice yield; whereas the application of oligosaccharides as plant growth regulators has been demonstrated to remarkably enhance crop tolerance to abiotic stresses. To investigate the potential growth-promoting effects of KP-priming (mixed-oligosaccharides, 1.12 mg mL−1) on rice seedlings under salinity (100 mmol L−1 NaCl) and alkalinity (10 mmol L−1 Na2CO3) stresses, plant morphology and physiology assessments, and transcriptome analyses were performed. The KP-priming significantly improved rice seedling tolerance to salinity and alkalinity stresses, evidenced by increases in plant height, dry matter weight, and fresh weight, and improved root morphology (root length, surface area) and vitality by 10.27–89.06%. Leaf cell membrane stability was improved in KP-priming by increasing the soluble sugar content and superoxide dismutase, peroxidase, and catalase activities by 2.74–97.32%, and reducing accumulation of malondialdehyde and hydrogen peroxide by 17.67–49.70%. KP-priming treatment significantly enhanced leaf photosynthetic capacity through promoting photosynthetic pigments and maximum photochemical efficiency by 2.34–135.76%, and enhancing leaf stomatal aperture by 21.58–75.84%. Transcriptomic analysis revealed that differentially expressed genes in response to KP-priming under salt and alkaline stresses were predominantly associated with photosynthetic pathways. Total 4125 (salinity) and 1971 (alkalinity) DEGs were identified under stresses compared to KP-priming. Transcriptional profiling of KP-priming-treated leaves demonstrated significant up-regulation of key photosynthetic genes, including OsRBCS5, PGR5, Se5, OsPORA, GRA78, OsLhcb7, and OsPS1-F. This coordinated gene expression was functionally associated with enhanced leaf photosynthesis capacity and mitigated oxidative damage through improved electron transport and reactive oxygen species scavenging mechanisms. Our findings demonstrated that KP-priming initiated a self-regulatory mechanism in plants, orchestrating a dual protective response that simultaneously mitigated oxidative damage while enhancing photosynthetic efficiency and stress resilience. This study provided initial insights into using KP-priming to alleviate salinity and alkalinity stresses and its underlying molecular mechanisms, which is valuable for both field management practices and understanding rice tolerance to abiotic stresses.